2018
DOI: 10.2147/ijn.s168570
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ultra-small monolayer graphene quantum dots by pyrolysis of trisodium citrate for fluorescent cell imaging

Abstract: BackgroundThe preparation and biological applications of ultra-small graphene quantum dots (GQDs) with accurate-controlled size are of great significance.MethodsHere in, we report a novel procedure involving pyrolysis of trisodium citrate and subsequent ultrafiltration for fabricating monolayer GQDs with ultra-small lateral size (1.3±0.5 nm).ResultsThe GQDs exhibit blue photoluminescence with peak position independent of excitation wavelength. The quantum yield of GQDs is measured to be 3.6%, and the average f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Hong et al reported a novel procedure to make the monolayer GQDs with the ultrasmall lateral dimension equal to 1.3 AE 0.5 nm which involved pyrolysing the trisodium citrate as well as the subsequent ultra ltration. 67 In a characteristic synthesis, 0.4 g of the dried VCX-72 carbon black has been reuxed in 100 mL of HNO 3 for 24 hours. In addition, an ultrasonic cell crusher has been used to treat the suspension at 950 W for ten minutes and then centrifuging has been done (8000 rpm) for ten minutes which led to get the supernatant.…”
Section: Synthesis Of Gqdsmentioning
confidence: 99%
“…Hong et al reported a novel procedure to make the monolayer GQDs with the ultrasmall lateral dimension equal to 1.3 AE 0.5 nm which involved pyrolysing the trisodium citrate as well as the subsequent ultra ltration. 67 In a characteristic synthesis, 0.4 g of the dried VCX-72 carbon black has been reuxed in 100 mL of HNO 3 for 24 hours. In addition, an ultrasonic cell crusher has been used to treat the suspension at 950 W for ten minutes and then centrifuging has been done (8000 rpm) for ten minutes which led to get the supernatant.…”
Section: Synthesis Of Gqdsmentioning
confidence: 99%
“…Instead of larger and few-layer-thick GQDs, monolayer ultrasmall GQDs were prepared following the pyrolysis approach, showing excitation wavelength-independent blue PL with a QY of 3.6%. Notably, due to the ultrasmall size, GQDs effectively penetrated into the nuclei of HeLa cells as monitored by tracking the blue fluorescence of GQDs during FL imaging (Hong et al, 2018). Considering the water solubility, excellent biocompatibility, and non-toxicity of GQDs, Ding et al developed a GQD-based theranostic nanoagent loaded with doxorubicin (DOX) (Ding et al, 2017).…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…The chemical linkage formation between hydroxyl groups from diethylene glycol and rhodamine carboxyl groups proves the arisen band at 1717 cm −1 , which is a characteristic for ester bonds. The resulting derivative-Rhod-OH-was further investigated over its chemical structure by 1 H-NMR and 13 C-NMR methods ( Figure 2). The chemical shifts presented in Table 1 correspond to the data obtained from FTIR analysis and clearly confirm that the N-(9-(2-carboxyphenyl)-6-(diethylamino)-3H-xanthen-3-ylidene)-Nethylethanaminium is a product of rhodamine b modification.…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupmentioning
confidence: 99%
“…A promising tool are quantum dots (QDs) which can be described as objects of the size below 10 nm with unique properties [1][2][3][4]. Since their development, they have been successfully used in optoelectronics [1], food packaging [5], metals detection [6][7][8], bioimaging [9][10][11][12][13][14], photocatalysis [15,16], sensing [17][18][19][20][21][22][23], cell labelling [24], or fluorescent inks and others [25,26]. The first-generation quantum dots are semiconductors of crystalline structure [3].…”
Section: Introductionmentioning
confidence: 99%